Retrospective evaluation of the Vidas HIV DUO test for simultaneous detection of anti-HIV antibody and p24 antigen - Poljak, Mario (Acta dermatovenerologica Alpina, Pannonica et Adriatica, 2002)
A fourth generation screening assay Vidas HIV DUO (bioMerieux, Lyon, France) which permits a simultaneous detection of anti-HIV-1/2/O antibodies and HIV-1 p24 antigen was evaluated on 927 serum samples with previously determined anti-HIV-1/2 status in a retrospective manner. The Vidas HIV DUO yielded sensitivity, specificity, positive and negative predictive value of 100%, 99.27%, 94.69% and 100%, respectively. The Vidas HIV DUO is a highly specific and sensitive anti-HIV screening assay, suitable for the implementation in theroutine laboratory diagnostics of HIV infection.
Keywords: Diagnosis; HIV; Hiv antibodies; Hiv infections; HIV infekcije; HIV, protitelesa; Hiv-1; Hiv-2; infekcije